Vulnerability of individuals on mental health medications to drug facilitated sexual assaults - Marie Lynam; David Keatley; Garth Maker; John Coumbaros (Forensic Science International: Synergy)
Drink spiking in social settings is one of the most pervasive forms of drug-facilitated sexual assault (DFSA). There are no current data in Australia on the rates of drink spiking or their associated assaults. There is also little known about the prevalence of different substances involved and how the current substance use trends compare to sexual assault trends. To explore this, a recalculation of sexual assault trends to estimate substance related sexual assault was performed. Data about recent trends of mental health prescriptions and sexual assault were obtained from the Australian Institute of Health and Welfare (AIHW). The analysis of these datasets highlighted that females are the highest consumers of antidepressants and benzodiazepines. Results also indicated a statistically significant positive correlation between females and a higher incidence of sexual assault (r = 0.996, p < .001). This paper demonstrates that females are at most risk of drug-drug interactions (e.g., diazepam and ketamine) with their medications due to the higher rate of prescriptions amongst this population, and therefore more vulnerable to both opportunistic and proactive DFSA. While these findings are preliminary and not causal, they highlight trends in need of further study.